Presence of sandfly-borne phleboviruses of two antigenic complexes (Sandfly fever Naples virus and Sandfly fever Sicilian virus) in two different bio-geographical regions of Tunisia demonstrated by a microneutralisation-based seroprevalence study in dogs - Sonia Sakhria; Sulaf Alwassouf; Wasfi Fares; Laurence Bichaud; Khalil Dachraoui; Cigdem Alkan; Ziad Zoghlami; Xavier de Lamballerie; Elyes Zhioua; Remi N Charrel (Parasites & Vectors, 2014)
Abstract Background Sandfly-borne phleboviruses are present in North Africa where they can infect humans in regions where Leishmania infantum, the causative agent of zoonotic visceral leishmaniasis in the Western Mediterranean basin is present affecting both humans and dogs. We investigated the capacity of dogs to be used as sentinels for sandfly-borne phleboviruses as previously shown for leishmaniasis. Findings A total of 312 sera were collected from guard dogs in two different bioclimatic regions (governorates of Kairouan and Bizerte) of Tunisia where zoonotic visceral leishmaniasis has been reported. These sera were tested for the presence of neutralising antibodies against 3 phleboviruses: Toscana virus, Punique virus and Sicilian virus. In the governorate of Kairouan, seroprevalence rates of 7.5%, 43.5%, and 38.1% were observed for Toscana, Punique and Sicilian virus, respectively. A high proportion of sera from the governorate of Bizerte were hemolyzed and showed high cytotoxicity for the cells and subsequently precluded detailed interpretation of this batch. However, validated results for 27 sera were in agreement with data observed in the governorate of Kairouan. Conclusions Toscana virus is present in the governorate of Kairouan but at a lower rate compared to Punique and Sicilian viruses. These three sandfly-borne phleboviruses can infect dogs. Direct detection and isolation of the viruses are now to be attempted in animals as well as in humans. Our findings showed that guard dogs are good sentinels for virus transmitted by sandflies and strongly suggested that the high seroprevalence rates observed in dogs merit further attention.